Enhancing Educational Quality Through Financial Transparency and Accountability: A Case Study of Pusat Pendidikan Warga Negara Indonesia - Sabaniah, Erna; Roesminingsih, Erny; Sholeh, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study investigates the role of financial transparency and accountability in enhancing the quality of education at Pusat Pendidikan Warga Negara Indonesia (PPWNI) in Klang, Selangor, Malaysia. The research aims to explore how effective financial management practices contribute to school quality improvement. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings reveal that transparent and accountable financial practices foster trust among stakeholders, optimize resource allocation, and enhance educational outcomes. A key novelty of this research lies in its focus on an expatriate community school, highlighting unique challenges and strategies in financial management within a multicultural and transnational context. The study contributes to the discourse on educational governance by emphasizing the critical role of financial integrity in achieving quality education. These insights provide valuable implications for policymakers and educational leaders aiming to replicate best practices in similar institutional settings.